KONTRIBUSI DAYA LEDAK TUNGKAI DAN KECEPATAN REAKSI TERHADAP KEMAMPUAN LARI 100 METER - Jamaluddin, Jamaluddin; Ad'dien, Ad'dien (UNIVERSITAS NEGERI MAKASSAR, 2020)
This research is a descriptive study with a correlational design. This study aims to determine whether there is a contribution to the explosive power of the legs and the reaction speed of the legs to the ability to run 100 meters. The population was students of the Sports Coaching Education Faculty of Sports Science, batch 2018, with a total sample of 30 people using random sampling techniques (randomly). The analysis technique used is regression and correlation analysis through the SPSS version 22.00 application program with a significant level of Î±0.05. The results showed that, (1). There is a contribution of the explosive power of the legs to the ability to run 100 meters, amounting to 55.7%. (2). There is a contribution of foot reaction speed to the ability to run 100, amounting to 51.7%. (3). There is a contribution of the explosive power of the legs and the reaction speed of the feet to the ability to run 100 meters, amounting to 64.5%.